Carnivorous sponges from the Australian Bathyal and Abyssal zones collected during the RV Investigator 2017 Expedition - Ekins, Merrick; Erpenbeck, Dirk; Hooper, John N.a. (Zootaxa, 2020)
This research presents 17 new species of carnivorous sponges from the family Cladorhizidae sampled at bathyal and abyssal depths off the east coast of Australia during the RV Investigator 2017 Abyss Expedition. The species are comprised of six genera: Abyssocladia escheri sp. nov., A. annae sp. nov., A. gliscofila sp. nov., Asbestopluma (Asbestopluma) maxisigma sp. nov., Cladorhiza australis nov. sp., C. poritea sp. nov., C. investigator sp. nov., C. moniqueae sp. nov., C. pentaeiros sp. nov., Chondrocladia (Chondrocladia) freycinetensis sp. nov., Ch. (Ch.) callistemonex sp. nov., Ch. (Ch.) zygainadentonis sp. nov., Lycopodina nikitawimandi sp. nov., L. helios sp. nov., L. cassida sp. nov., L. brochidodroma sp. nov. and Euchelipluma claudochela sp. nov. Only three carnivorous species, A. desmophora, As. (As.) desmophora and C. (Meliiderma) tasmaniensis, have been recorded from Australia previously. This expedition also recovered two described species commonly recorded from the Southern Hemisphere Ch. (Ch.) clavata and L. calyx. This paper also redescribes two species from the South Pacific i.e. C. mirabilis and C. similis.